Carbon payments as a safeguard for threatened tropical mammals - Venter, O.; Meijaard, E.; Possingham, H.P.; Dennis, R.A.; Sheil, Douglas; Wich, S.; Hovani, L.; Wilson, K.A. (2009)
One reason for the rapid loss of species-rich tropical forests is the high opportunity costs of forest protection. In Kalimantan (Indonesian Borneo), the expansion of high-revenue oil palm (Elaeis guineensis) plantations currently threatens 3.3 million ha of forest. We estimate that payments for Reduced Emissions from Deforestation and forest Degradation (REDD) could offset the costs of stopping this deforestation at carbon prices of US$ 10-33 per tonne of CO2, or $ 2-16 per tonne if forest conservation targets only cost-efficient areas. Forty globally threatened mammals are found within these planned plantations, including the Bornean orangutan (Pongo pygmaeus) and Borneo pygmy elephant (Elephas maximus borneensis). Cost-efficient areas for emissions reductions also contain higher-than-average numbers of threatened mammals, indicating that there may be synergies between mitigating climate change and conserving biodiversity. While many policy and implementation issues need clarification, our economic assessment suggests that REDD could offer a financially realistic lifeline for Kalimantan's threatened mammals if it is included in future climate agreements.